2013
DOI: 10.1002/jcp.24402
|View full text |Cite
|
Sign up to set email alerts
|

miR‐10a restores human mesenchymal stem cell differentiation by repressing KLF4

Abstract: miRNAs have recently been shown to play a significant role in human aging. However, data demonstrating the effects of aging-related miRNAs in human mesenchymal stem cells (hMSCs) are limited. We observed that hMSC differentiation decreased with aging. We also identified that miR-10a expression was significantly decreased with age by comparing the miRNA expression of hMSCs derived from young and aged individuals. Therefore, we hypothesized that the downregulation of miR-10a may be associated with the decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 55 publications
(61 reference statements)
2
39
0
Order By: Relevance
“…(72) In this study, we observed higher levels of miR-486-5p, miR-378a-5p, and miR-196b-5p in DMFx women compared to fracture-free DM subjects. Similar expression pattern and fold changes were reported by Li and colleagues, (73) who compared miRNA expression levels in bone marrow mesenchymal stem cells from 80-year-olds to those of young, 30-year-old human subjects. Our DFMx patients are not significantly, but are on average three years older than our DM subjects, which could explain the higher expression-rate of senescence-related miRNAs in their serum.…”
Section: Discussionsupporting
confidence: 76%
“…(72) In this study, we observed higher levels of miR-486-5p, miR-378a-5p, and miR-196b-5p in DMFx women compared to fracture-free DM subjects. Similar expression pattern and fold changes were reported by Li and colleagues, (73) who compared miRNA expression levels in bone marrow mesenchymal stem cells from 80-year-olds to those of young, 30-year-old human subjects. Our DFMx patients are not significantly, but are on average three years older than our DM subjects, which could explain the higher expression-rate of senescence-related miRNAs in their serum.…”
Section: Discussionsupporting
confidence: 76%
“…Induction of premature senescence in HDFs was accompanied by upregulation of p16 INK4a ; an important downstream target of BMI1 and a major regulator of senescence [23]. It has been reported that miR-141-3p, miR-10a and miR-199b-5p regulate senescence in human mesenchymal stem cells by targeting ZMPSTE24, KLF4 or LAMC networks, respectively [24][25][26]. Thus, we focused on miRNA as a candidate regulator of ROCK1 during TSPC aging.…”
Section: Discussionmentioning
confidence: 97%
“…This suggests that these miRNAs are regulated by p53 during reprogramming by complex mechanisms. An example is miR-10a that on the one hand is known to promote the differentiation of human mesenchymal stem cells 69 and on the other contributes to cancer development. 70, 71 This miR is downregulated during reprogramming of p53 wt cells, but upregulated in cells expressing mutant p53.…”
Section: Resultsmentioning
confidence: 99%